Effectiveness of terrestrial protected areas for conservation of lake fish communities. Issue 3 (25th January 2018) - Chu, Cindy; Ellis, Lucy; de Kerckhove, Derrick T.
Abstract: Freshwater protected areas are rare even though freshwater ecosystems are among the most imperiled in the world. Conservation actions within terrestrial protected areas (TPAs) such as development or resource extraction regulations may spill over to benefit freshwater ecosystems within their boundaries. Using data from 175 lakes across Ontario, Canada, we compared common indicators of fish‐assemblage status (i.e., species richness, Shannon diversity index, catch per unit effort, and normalized‐length size spectrum slopes) to evaluate whether TPAs benefit lake fish assemblages. Nearest neighbor cluster analysis was used to generate pairs of lakes: inside versus outside, inside versus bordering, and bordering versus outside TPAs based on lake characteristics. The diversity and abundance indicators did not differ significantly across comparisons, but normalized‐length size spectrum slopes (NLSS) were significantly steeper in lakes outside parks. The latter indicated assemblage differences (greater abundances of small‐bodied species) and less‐efficient energy transfer through the trophic levels of assemblages outside parks. Although not significantly different, pollution‐ and turbidity‐tolerant species were more abundant outside parks, whereas 3 of the 4 pollution‐intolerant species were more abundant within parks. Twenty‐one percent of the difference in slopes was related to higher total dissolved solids concentrations and angling pressure. Our results support the hypothesis that TPAs benefit lake fish assemblages and suggest that NLSS slopes are informative indicators for aquatic protected area evaluations because they represent compositional and functional aspects of communities. Abstract : Article impact statement : Outside parks, abundances of small‐bodied fish are greater and energy transfer through trophic levels of assemblages is less efficient. Abstract : Efectividad de las Áreas Protegidas Terrestres para la Conservación de las Comunidades de Peces Lacustres Resumen: Las áreas protegidas en cuerpos de agua dulce son raras a pesar de que los ecosistemas de agua dulce están entre los más amenazados del mundo. Las acciones de conservación dentro de las áreas protegidas terrestres como las regulaciones del desarrollo o de la extracción de recursos pueden transmitirse para beneficio de los ecosistemas de agua dulce dentro de sus límites. Con datos de 175 lagos en Ontario, Canadá, comparamos los indicadores comunes del estado de la composición de peces (es decir, riqueza de especies, índice de diversidad Shannon, esfuerzo de captura por unidad, y espectros de tamaño y longitud normalizada) para evaluar si las áreas protegidas terrestres benefician al ensamblaje de peces lacustres. Se utilizó el análisis de clúster de vecinos próximos para generar pares de lagos: dentro versus fuera, dentro versus limitante, y limitante versus fuera de las áreas protegidas terrestres con base en las características del lago. Los indicadores de diversidad y abundancia no difirieron significativamente entre las comparaciones, pero las pendientes del espectro de tamaño y longitud normalizada (NLSS, en inglés) fueron significativamente más inclinadas en los lagos externos a los parques. Lo anterior indicó diferencias en la composición (mayor abundancia de especies de talla pequeña) y una transferencia de energía menos eficiente a través de los niveles tróficos en los ensamblajes fuera de los parques. Aunque no fueron significativamente diferentes, las especies tolerantes a la contaminación y a la turbidez fueron más abundantes fuera de los parques, mientras que tres de las cuatro especies intolerantes a la contaminación fueron más abundantes dentro de los parques. El 21% de la diferencia en las pendientes estuvo relacionado con concentraciones mayores totales de sólidos disueltos y la presión de pesca. Nuestros resultados respaldan la hipótesis de que las áreas protegidas terrestres benefician a la composición de peces lacustres y sugieren que las inclinaciones NLSS son indicadores informativos para las evaluaciones de áreas protegidas acuáticas pues representan los aspectos funcionales y de composición de las comunidades. 摘要: 淡水生态系统是世界上最受威胁的生态系统之一, 然而淡水保护区却仍然匮乏。由于范围部分重叠, 针对陆地保护区的保护行为, 如制定严格的开发或资源开采法规, 有时也能够为淡水生态系统带来一定的保护效应。我们分析了加拿大安大略省175个湖泊的数据, 并对反映鱼类集群状况的一系列通用指标 (如, 物种丰富度, 香农多样性指数, 单位渔获量, 标准化长度谱等) 进行比较, 以评估陆地保护区对该地湖泊鱼类群落的保护效力。根据湖泊的分布特征, 我们利用最短距离聚类法将其分为:分布在陆地保护区内部或外部的湖泊, 分布在陆地保护区中心或边缘的湖泊, 以及分布在陆地保护区边缘或外部的湖泊等不同比较组进行研究。结果表明, 多样性和丰度指标在比较中没有显著差别, 但陆地保护区外湖泊的标准化长度斜率 (NLSS) 数值更高。该指标显示保护区外湖泊鱼类群落中有更多的小体型鱼类, 而不同营养级间的能量转换效率更低。我们还发现耐污浊鱼类在保护区外湖泊中更为丰富, 而对污染敏感的四种鱼类中有三种则在保护区内湖泊中数量更多, 但这些差异没有达到显著标准。经分析, NLSS 21%的斜率差异是由更高的溶解性总固体浓度及鱼获压力所致。我们的研究结果支持陆地保护区有益于湖泊鱼类群落保护这一假设。同时, 由于NLSS斜率可以正确反映鱼类群落的组成性和功能性特征, 我们认为NLSS是评价水生生物保护区保护效力的可靠指标。[翻译: 胡怡思; 审校: 魏辅文 ]